Recurrence of uterine myoma after laparoscopic myomectomy: What are the risk factors? - Mitsuru Shiota; Yasushi Kotani; Masahiko Umemoto; Takako Tobiume; Hiroshi Hoshiai (Wolters Kluwer Medknow Publications, 2012)
Objective: Uterine myoma is a common gynecologic disease. Myomectomy is selected to preserve the uterus, and with recent advances in laparoscopic technology, laparoscopic myomectomy (LM) has become a common treatment. However, myoma can recur after LM, and to date, reports on post-LM recurrence rates and risk factors have been inconsistent. This retrospective study examines post-LM recurrence rates and the possible risk factors for recurrence. Materials and Methods: Between 1995 and 2010, 250 patients who underwent LM at a single institution were followed from the postoperative sixth month to the fifth year semiannually for recurrence by ultrasound/magnetic resonance imaging (MRI). Mean age, body mass index (BMI), preoperative gonadotropin-releasing hormone agonist (GnRHa) therapy, surgical time, blood loss, number of removed myomas, and largest myoma diameter were compared between patients with recurrence and those without. Recurrence rates were also investigated by individual risk factors, including patient age, GnRHa therapy, number of removed myomas, and largest tumor diameter. Results: Cumulative post-LM recurrence rates were 15.3%, 43.8%, and 62.1% at postoperative years 1, 3, and 5, respectively. There were significant differences in surgical time, blood loss, and number of removed myomas between patients with recurrence and those without. Analysis of risk factors revealed significant correlation between recurrence rates and patient age, number of myomas, and myoma size. Conclusion: Risk of post-LM recurrence increases over time. Risk factors are age, myoma size, and number of tumors. Particular attention to recurrence is required for patients with uterine myomas of ≥10 cm diameter, with numerous myomas, and those age 35 years or older.